2016
DOI: 10.5194/isprs-archives-xli-b1-1051-2016
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Image-Derived and Pos-Derived Features for Image Blur Detection

Abstract: Commission I, ICWG I/VbKEY WORDS: Position and Orientation System (POS), Unmanned Aerial Vehicle (UAV), blur image detection, degree of motion blur ABSTRACT:The image quality plays an important role for Unmanned Aerial Vehicle (UAV)'s applications. The small fixed wings UAV is suffering from the image blur due to the crosswind and the turbulence. Position and Orientation System (POS), which provides the position and orientation information, is installed onto an UAV to enable acquisition of UAV trajectory. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Teo and Zhan 15 Liu et al 14 Xu et al 11 Rugna and Konik 13 Huang et al 18 Ours It is found that accuracy of these datasets is all greater than 94%, which again demonstrates our method has superior generalization ability and satisfactory robustness. Considering blurry images and sharp images separately, all precision and recall are greater than 94% except GoPro dataset.…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…Teo and Zhan 15 Liu et al 14 Xu et al 11 Rugna and Konik 13 Huang et al 18 Ours It is found that accuracy of these datasets is all greater than 94%, which again demonstrates our method has superior generalization ability and satisfactory robustness. Considering blurry images and sharp images separately, all precision and recall are greater than 94% except GoPro dataset.…”
Section: Methodsmentioning
confidence: 59%
“…Liu et al 14 focused their attention on low-level features and proposed a blur discrimination method through some image features, including local auto-correlation congruency, gradient histogram span, spectrum slope, and maximum saturation. Teo and Zhan 15 proposed a detection method for the blurry image by integrating image-derived features and position and orientation system-derived features. Wang et al 16 proposed a blur detection method for iris image based on local features, which are generated by radial symmetry transform and support vector machine.…”
Section: Methods Based On Hand-extracted Featuresmentioning
confidence: 99%
See 1 more Smart Citation